A natureza da verticalização no processo de reprodução do espaço urbano em Palmas-TO - Rodrigues, Marcely Pereira da Silveira (Universidade Federal do Tocantins, 2017)
This research deals with the verticalization process that has, in recent years, been taking place in Palmas, the city designed to be the capital of the state of Tocantins. Verticalization should be perceived as the construction of buildings with many floors, enabling the creation of urban ground, since, in the same land area, flooring overlay allows the multiplication of the units built. In this perspective, this dissertation intends to understand the process of verticalization in Palmas, checking its specificities from the urban project to its current significance in the process of (re) production of the urban space in this city. Therefore, the research took into account data from the urban project and the legislation that regulates the verticalization in the city as well as collected data on completed vertical buildings and in construction in the city until 2015 and information about the agents and resources involved in this vertical production. The information was obtained through desk and field research. The obtained results show that verticalization was envisaged in the urban project of this capital, but its production took place discreetly up to 2000. In the period between the years 2001 and 2010, verticalization became a little more expressive, but it was characterized by the predominance of smaller buildings with up to sixteen floors. Since 2010, a very significant increase in vertical constructions became underlined, supported by the favorable economic climate for the sector (real estate boom) when there was an increase on the release of funds for construction. In the last four years, more buildings were built than the sum of buildings from previous periods. However, this verticalization not only stands out concerning the increase in the number of buildings, but also with regard to the dispersion of low-rise buildings (up to four floors), the spatial concentration of tall buildings (between five forty floors), the diversification of the buildings produced and the participation of new producing agents in the process. Thus, ground manufacture became fundamental data in the process of (re) production of this urban space, promoting the restructuring of the spatial configuration of the city, since verticalization reinforced the urban territorial expansion trends in Palmas, but on a broader scale, added, to the horizontal phenomenon, the vertical phenomenon, by the unfolding, and by the multiplication of the land base. This process thus reveals a dialectic pair - urban horizontal expansion and vertical urban expansion, which reinforces in the production of this space, both land interests, construction and real estate, in addition to the interests of the financial sector.